2020
DOI: 10.1007/s40430-020-02319-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of convection heat transfer in a circular copper tube using graphene oxide nanofluid

Abstract: To able to employ nanofluids in engineering applications, it is essential to investigate heat transfer properties in addition to thermophysical characteristics. In this work, the convection heat transfer coefficient of graphene oxide-distilled water nanofluid along a circular copper tube having a constant heat flux at the outside surface has been investigated both numerically and experimentally under turbulent flow regime. While the nanofluid convection heat transfer and head loss of pressure have been evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…Particle growth is difficult to control, including optimization of particle sizes and their shapes and agglomerative formations reduce in the co-precipitation. This procedure is similar with graphene oxide nanoparticle synthesis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Particle growth is difficult to control, including optimization of particle sizes and their shapes and agglomerative formations reduce in the co-precipitation. This procedure is similar with graphene oxide nanoparticle synthesis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Bu eşitlikte, ρ akışkanın yoğunluğunu (kg/m 3 ), φ nanoparçacık konsantrasyonu ifade ederken, p, nf ve bf ise sırasıyla nanoparçacık, nanoakışkan ve su akışkanını belirtmektedir [17,18]. Nanoakışkanın Özgül Isısı [17,18,19] (1…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Ajeel et al [50] numerically examined the hydraulic and thermal properties of nanofluids (ZnO-water) for turbulent flow with L-shaped baffles in a curved wavy channel and reported that the baffles and nanofluids have a considerable influence on increasing the heat transfer rate. Experimental investigations of convection heat transfer in a circular copper tube using graphene oxide nanofluid carried out by Karabulut et al [51][52][53] and Kilinc et at. [54].…”
Section: Introductionmentioning
confidence: 99%